Studies Abouut the Differentiated Disciplinary Regime Guided in International Understanding and Human Rights - Fernanda Eloise Schmidt Ferreira Feguri; Roberto Feguri (Revista de Criminologias e Politicas Criminais, 2015)
The work has the objective to analyze the Differentiated Disciplinary Regime from the perspective of human rights, checking their application in the Brazilian scenario, as well as bringing its consequences and the international positioning of the Courts and organizations about its applicability. Initially, the research brings a brief historical view of the emergence of such a system and then shows its consequences to those with prolonged and strict solitary confinement are submit. The whole work settles on the analysis of the application of Differentiated Disciplinary Regime face the principles of human dignity and humanity of penalties. It also analyzes the Differentiated Disciplinary Regime on the study of the functions of feathers, only praising his retributive content and discarding rehabilitation opportunities for graduates for prisoners, which causes or contributes significantly to the process of social exclusion.